First record of the genus Acrodactyla Haliday (Hymenoptera: Ichneumonidae: Pimplinae) from Vietnam, with descriptions of six new species - Pham, Nhi Thi; Broad, Gavin R.; Matsumoto, Rikio; Böhme, Wolfgang (Zootaxa, 2012)
Six new Acrodactyla species are described and illustrated from Vietnam based on the Ichneumonidae collection depositedat the Netherlands Centre for Biodiversity, Naturalis, Netherlands and the Osaka Museum of Natural History, Japan: A.maiphuquyi sp. nov., A. elongata sp. nov., A. shawi sp. nov and A. tami sp. nov. collected from Lao Cai Province at anelevation of 1,700–2,320 m a.s.l; A. lachryma sp. nov. collected from Chu Mom Ray NP, Kon Tum Province at an eleva-tion of 700–900 m a.s.l; and A. phuthoensis sp. nov. collected from Xuan Son NP, Phu Tho Province at an elevation of350–400 m a.s.l. Acrodactyla maiphuquyi sp. nov., A. elongata sp. nov. and A. tami sp. nov. belong to the degener group; A. lachryma sp. nov., A. phuthoensis sp. nov. and A. shawi sp. nov. belong to the quadrisculpta group.